SIMULASI ANTRIAN DENGAN PELAYANAN SIKLIK DALAM SISTEM PERSIMPANGAN BERSINYAL - , M. DERMAWAN MULYODIPUTRO; , Prof. 2. Drs. Subanar, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Simulation was implemented by modeling the queue with cyclic service in traffic-light system. The service policies are exhaustive and gated. The model is the M/M/1 queue, where the arrival rate is Poisson distribution and the services rate is Exponential distribution. In the gated service policy, the server serves only vehicles that come before the green signal appears at an intersection. Considered that there are 2 types of exhaustive policy in the traffic-light system, namely normal exhaustive (vehicles only served during the green signal is still active), and exhaustive (where there is the addition of the duration of the green signal at the intersection, when the duration of the green signal at an intersection finished). Results of this queue simulation program are to obtain the characteristics and performance of the system, i.e. the average number of vehicles in the intersection and in the system, and the average waiting time of vehicles in the intersection and in the system, as well as system utilities. Then from these values, it will be known which of the cyclic service policies (normal exhaustive, exhaustive and gated) is most suitable when applied to a traffic-light system.